Normal Complications and Abnormal Assumptions After Perinatal Death. Issue 1 (January 2019) - Cacciatore, Joanne; Thieleman, Kara
Abstract : Abstract: There are several ways, clinically, to approach grief after perinatal death, including from a humanistic or a medicalized perspective. The death of a baby is complicated. The loss is an embodied one that incites deep psychological wounds and can be isolating for many parents. Parents process their grief experiences within a sometimes oppressive social context that either sees their expressions of loss as a normal response to an abnormal tragedy or as pathology. Several diagnostic categories have been proposed relative to the traumatic grief experiences of grieving parents that potentially affect them. We explore this nomenclature and, through the lens of a Social-Cognitive Processing Model, examine social support, attitudes, context, and oppressive interpersonal and social structures that affect parents. Clinical implications are discussed. Abstract : Death of a baby can be traumatizing for the parents and family. Some expressions of grief that have been considered pathologic in the past are likely normal in this population. Diagnosis categories of perinatal grief are discussed and clinical recommendations offered.